2014
DOI: 10.1186/1471-2334-14-263
|View full text |Cite
|
Sign up to set email alerts
|

Combined immunization using DNA-Sm14 and DNA-Hsp65 increases CD8+ memory T cells, reduces chronic pathology and decreases egg viability during Schistosoma mansoniinfection

Abstract: BackgroundSchistosomiasis is one of the most important neglected diseases found in developing countries and affects 249 million people worldwide. The development of an efficient vaccination strategy is essential for the control of this disease. Previous work showed partial protection induced by DNA-Sm14 against Schistosoma mansoni infection, whereas DNA-Hsp65 showed immunostimulatory properties against infectious diseases, autoimmune diseases, cancer and antifibrotic properties in an egg-induced granuloma mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The viability of the eggs may influence the pathogenesis in the UB but it is unknown. One study described viable and dead eggs were mixed in the intestinal tissue of S. mansoni infected mice [21]. The mice were kept for 69 days after the infection and about 1/4 of eggs were found dead in the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The viability of the eggs may influence the pathogenesis in the UB but it is unknown. One study described viable and dead eggs were mixed in the intestinal tissue of S. mansoni infected mice [21]. The mice were kept for 69 days after the infection and about 1/4 of eggs were found dead in the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The worms were washed and counted using a dissecting microscope. Intestinal egg viability was measured in fragments of the intestine (terminal ileum), as previously described ( 24 ). The fragments were examined with an optical microscope (100 ×), and 200 eggs/mouse were counted and classified according to the developmental stage as follows: (i) viable immature eggs (1st to 4th stage), (ii) viable mature eggs or (iii) dead eggs.…”
Section: Methodsmentioning
confidence: 99%
“…Another interesting data obtained by these investigations is that this immunotherapy might be a valuable tool to shorten the duration of antibacterial treatment (20,39) in addition to enhancing the response against latent TB and MDR-TB (39,40). The results also suggest that DNAhsp65 is able to prevent TB reactivation in immunosuppressed animals (39,40) and could be administered in helminth coinfection cases (42)(43)(44).…”
Section: Prophylactic and Therapeutic Effects Of Dnahsp65 Against Infectious Diseases Tuberculosismentioning
confidence: 90%
“…In TB, the results obtained with the DNAhsp65 vaccine containing the gene that expresses the mycobacterial heat shock protein hsp65 showed that this plasmid DNA construction is a product of radical innovation because it acts in all essential and possible points for the control of disease; acts in prevention (29)(30)(31)(32)(33)(34)(35)(36); can be used as a BCG vaccine boost (38,67,70); acts in the immunotherapy of chronic TB (38), MDR-TB (39-41), and TBL (39)(40)(41); can be used concomitantly with antimycobacterial drugs to enhance the therapeutic and immunotherapeutic action (20,39); prevents the reactivation of the infection (39,40); and can act on those individuals with compromised immune systems, as in helminth infections (42)(43)(44).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation